IMPROVEMENT OF CHILDREN’S LANGUAGE SKILLS THROUGH SINGING ACTIVITIES - Lily Yuntina (Department of English Education, Universitas Panca Sakti Bekasi, 2021)
Education as a dynamic process in which children develop according to the inner terms of their lives, with their